Would Malaysian Customers Buy Fashion Goods Online? An exploratory study on the prospect of fashion e-tailing in Malaysia - Mak, Sook Han (2008)
With the growing interest in online shopping along with the increase in internet penetration within the country, it is expected that more product categories will be offered online by local retailers. In the Malaysian retail scene, fashion is set to be one among the many potential new categories making its presence felt in the online channel soon. Taking cue from this new development, an exploratory research is conducted to understand the views of Malaysian consumers with the prospect of buying fashion goods online. The research aims to explore the market potential of retailing fashion goods online or known as fashion e-tailing in Malaysia. In this study, the level of interest in buying fashion goods online; attitudes; behaviour; perception of risks; and key factors that influence Malaysia consumers in deciding whether to buy or not to buy fashion goods online are examined. The contribution of multichannel strategy in driving the acceptance of online shopping for fashion goods are also explored in the research. The survey results have shown a low level of interest among the respondents in buying fashion goods online, attributed to the high level of perceived risks associated with buying fashion goods online. Based on the findings, recommendations of appropriate business strategies are extended with aims to facilitate the acceptance of fashion e-tailing in Malaysia.